Análise do comportamento transitório de geradores distribuídos eólicos e fotovoltaicos conectados num mesmo alimentador - Bainy, Rômulo Gonçalves (2015)
This work evaluated the effect of the variation of some factors over the transient behavior of a feeder from a Distribution Power System where there are Distributed Generator (DG) connected. Two types of distributed generation were evaluated, which are photovoltaic and wind power. The chosen Distribution Power System has 32 nodes and was presented by (de Abreu, 2005) and (Salim, 2010). First of all, this feeder was characterized and the nodes were separated on four clusters, comply some electric characteristics from each one. Each cluster has a chosen node that represents the center of the group from the cluster, which resulted on four candidates nodes. Than, it was time to build the scenarios for simulation, they were made by two candidate node and fault node, which means that there are six possible scenarios. To chose the fault node, there is some premises: None of GD can generate on a islanded operation; It is not necessary that all scenarios has the same fault node; and, the more important one, the fault node must have fault current similar on all scenarios. The studied factors were: Loading of the feeder; Power factor of the loads; X/R relation of lines; GFV conexion; FSIG conexion. The simulation evaluated the influence of each factors. Among the five , only two showed influence in the transient behavior of the system: the connection ratio X/R and the FSIG conexion . The other three did not shown influence. Thus, the two factors correspond to valuable study object , and should be considered when evaluating the transient behavior at Distribution System with DG.